The meeting of business and spirituality: its evolutionary significance - Srinivasan, M.S. (2003)
Spirituality is now a much talked about subject. All over the world, after a long region of heavy and soul-stifing materialism, people are seeking for a higher meaning in work and life, beyond the mundane and material aims. So religion and spirituality are coming back with the message of hope and peace. Business, which is a leading institution of our age and employs a large chunk of humanity, cannot escape from this new worldwide trend. Thus, the meeting of business and spirituality is already happening. This article examines the evolutionary significance of this meeting in the light of Sri Aurobindo's spiritual vision. - Reproduced.
Keywords: Spiritualism